Effect of Plastic Mulch Type on Fomesafen Dissipation in Florida Vegetable Production Systems. Issue 1 (14th August 2017) - Reed, Thomas V.; Boyd, Nathan S.; Wilson, P. Christopher; Dittmar, Peter J.
Abstract : Mulches used in plasticulture systems could decrease dissipation of fomesafen, a protoporphyrinogen oxidase inhibitor, and dissuade producers from using the herbicide for fear of crop injury in subsequent growing seasons. Field experiments were conducted in Balm, FL, in 2015 and 2016 to investigate the effect of different plastic mulches on fomesafen dissipation, squash tolerance, and efficacy on purple nutsedge. Squash was injured less than 5% from fomesafen applications. The use of plastic mulches reduced purple nutsedge density at transplant by 60% compared with the no-mulch treatment. At transplant, treatments with low-density polyethylene mulch (LDPE), virtually impermeable film (VIF), and totally impermeable film (TIF) mulch had greater than 2-fold the fomesafen concentrations than treatments with clear or no mulch. At harvest in 2015, LDPE, VIF, and TIF treatments had greater fomesafen concentrations than clear and no-mulch treatments; however, concentrations in 2016 were similar for all treatments. Fomesafen can persist at high concentrations throughout the growing season in Florida plasticulture possibly limiting producer options for crop rotation and the use of cover crops.